Successful conservative management of delayed perforation following endoscopic submucosal dissection of the esophagus: A case report - Sachiyo Onishi; Jun Takada; Kiichi Otani; Naoya Masuda; Hiroki Taniguchi; Kentaro Kojima; Masaya Kubota; Takashi Ibuka; Takuji Iwashita; Masahito Shimizu (DEN Open)
Abstract Delayed perforation after esophageal endoscopic submucosal dissection is a rare complication that may result in severe outcomes. Here, we report a case of delayed perforation that was successfully managed with conservative treatment. A 72‐year‐old male with hypertensive renal failure and on maintenance hemodialysis underwent endoscopic submucosal dissection for a 2/3 circumferential superficial esophageal cancer in the middle thoracic esophagus, involving resection of 4/5 of the esophageal circumference. Locoregional steroid injections were administered after resection to prevent stenosis. No perforation occurred during the procedure; however, delayed perforation was identified on postoperative day 3. Endoscopy revealed necrosis and brittleness in a large area of the post‐endoscopic submucosal dissection ulcer. The patient developed fever and mediastinal emphysema, and endoscopic attempts to close the perforation were unsuccessful. Conservative management—including fasting, antibiotics, and subsequent drainage—was initiated. The patient's condition improved with drainage tube placement, enteral nutrition, and antibiotic administration. A follow‐up computed tomography scan on postoperative day 56 confirmed the resolution of mediastinal emphysema, and endoscopy revealed that the perforation healed with scarring. This case highlights that surgery may be avoided if appropriate treatment is initiated as early as possible, including drainage to prevent exposure to gastric and intestinal fluids, early initiation of enteral nutrition, rehabilitation to maintain strength, and blood transfusions as supportive care.